THE USE OF SKIMMING TO TEACH EXTENSIVE READING - Tiara Nove Ria (Majalah Ilmiah Inspiratif, 2016)
Teaching reading in a second language is not easy as teaching in students’ first language. There are three reasons why teacher should teach reading to their students. Using skimming, the students will get the main idea quickly. . Skimming is helpful when she or he wants to know the point of view of the text. It is not necessary to read word by word. There are many strategies that can be used when skimming. Some people read the first and last paragraphs using headings, summarizes and other organizers as they move down the page or screen. You might read the title, subtitles, subheading, and illustrations. Consider reading the first sentence of each paragraph. Reading extensively means reading widely and in quantity. By reading what students choose and enjoying their reading students have a great deal of flexibility, which caters to the different needs and interests of individual students and allow them to develop their reading competence at their own rates.Keywords: skimming, teaching reading, extensive reading